Digital Literacy Analysis of Chemistry Education Students in Using the ChemDraw Application - Ella Izzatin Nada; Wiwik Kartika Sari (Program Studi Pendidikan Kimia FKIP Universitas Sebelas Maret, 2020)
Students digital competence abilities can be measured using the individual competence framework. There are five indicators used: information, communication, content creation, safety, and problem-solving. This study analyses students digital literacy profile with high, medium, and low ChemDraw skills. This research is a qualitative descriptive study. The trial was conducted on 25 Chemistry Education Students at UIN Walisongo Semarang with high, medium and low ChemDraw skills. Data were obtained using ChemDraw test instruments, observation and questionnaires. The data obtained were analysed based on digital literacy indicators to obtain student digital literacy profiles. The results showed that the digital literacy level of students with high ChemDraw skills had a moderate level of digital competence. Students with medium ChemDraw skills have a moderate level of digital competence. Meanwhile, students with low ChemDraw skills have a low level of digital competence